Machine learning-based prediction of early neurological deterioration after intravenous thrombolysis for stroke: insights from a large multicenter study - Wen, Rui; Wang, Miaoran; Bian, Wei; Zhu, Haoyue; Xiao, Ying; Zeng, Jing; He, Qian; Wang, Yu; Liu, Xiaoqing; Shi, Yangdi; Zhang, Linzhi; Hong, Zhe; et al. (Frontiers in Neurology, 2024)
Background: This investigation seeks to ascertain the efficacy of various machine learning models in forecasting Early Neurological Deterioration (END) following thrombolysis in patients with acute ischemic stroke (AIS). Methods: Employing data from the Shenyang Stroke Emergency Map database, this multicenter study compiled information on 7,570 AIS patients from 29 comprehensive hospitals who received thrombolytic therapy between January 2019 and December 2021. An independent testing cohort was constituted from 2,046 patients at the First People's Hospital of Shenyang. The dataset incorporated 15 pertinent clinical and therapeutic variables. The principal outcome assessed was the occurrence of END post-thrombolysis. Model development was executed using an 80/20 split for training and internal validation, employing classifiers like logistic regression with lasso regularization (Lasso regression), Support Vector Machine (SVM), Random Forest (RF), Gradient-Boosted Decision Tree (GBDT), and Multi-Layer Perceptron (MLP). The model with the highest Area Under the Curve (AUC) was utilized to delineate feature significance. Results: Baseline characteristics showed variability in END incidence between the training (n=7,570; END incidence 22%) and external validation cohorts (n=2,046; END incidence 10%; P<0.001). Notably, all machine learning models demonstrated superior AUC values compared to the reference model, indicating their enhanced predictive capacity. The Lasso regression model achieved the highest AUC at 0.829 (95% CI: 0.799-0.86; P<0.001), closely followed by the MLP model with an AUC of 0.828 (95% CI: 0.799-0.858; P<0.001). The SVM, RF, and GBDT models also showed commendable AUCs of 0.753, 0.797, and 0.774, respectively. Decision curve analysis revealed that the SVM and MLP models demonstrated a high net benefit. Feature importance analysis emphasized 'Onset To Needle Time' and 'Admission NIHSS Score' as significant predictors. Conclusions: Our research establishes the MLP and Lasso regression as robust tools for predicting early neurological deterioration in acute ischemic stroke patients following thrombolysis. Their superior predictive accuracy, compared to traditional models, highlights the significant potential of machine learning approaches in refining prognosis and enhancing clinical decisions in stroke care management. This advancement paves the way for more tailored therapeutic strategies, ultimately aiming to improve patient outcomes in clinical practice.